Eﬀectiveness of Manipulative Therapy on Neck Pain, Function and Disability. A Systematic Review - Nan Xu; Elif Nur Surucu (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background: Neck pain is a common musculoskeletal issue affecting people worldwide, and manipulative therapy is implemented as a treatment for it.